Phytoremediation of wastewater using aquatic plants, A review - Zahra Mohebi (Razi University, 2021)
Disposal of waste products and residuals into the natural water bodies can havefatal consequences for aquatic ecosystems, posing severe threats to naturalhabitats and human health. Natural treatment systems are the most suitabletreatment technologies for various types of wastewaters, which has attracted muchattention in recent years. Phytoremediation is a plant-based technique used toeliminate or recover surplus nutrients in contaminated environments. The use ofaquatic plants in wastewater phytoremediation is very efficient due to they have avery significant ability for assimilating and degrading contaminants (e.g., nitrates,phosphates, and heavy metals). Phytoremediation is a relatively new technologythat is considered as an operational, efficient, new, and environmentally friendlytechnology that is still in the early stages of development and optimization. Itsapplication on a large scale is still limited. It should also be noted that a clear visionof this innovation should be taken into account and, accurate data should be madeavailable to the public as it will enhance its efficiency as a manageable solution inthe worldwide. Additionally, phytoremediation has been evaluated as a separatelow-tech and environmentally friendly green option compared to the existingtechnologies. The present study attempts to review the recently published literatureto explain phytoremediation technology and its advantages in purifying water andwastewater.